Fraud, investments and liability regimes in payment platforms - Anna Creti; Marianne Verdier (European Central Bank (ECB), 2011)
In this paper, we discuss how fraud liability regimes impact the price structure that is chosen by a monopolistic payment platform, in a setting where merchants can invest in fraud detection technologies. We show that liability allocation rules distort the price structure charged by platforms or banks to consumers and merchants with respect to a case where such a responsibility regime is not implemented. We determine the allocation of fraud losses between the payment platform and the merchants that maximises the platform's profit and we compare it to the allocation that maximises social welfare.
Keywords: G21; L31; L42; 330; fraud; interchange fees; liability; Payment card systems; two-sided markets